Occupation versus environmental factors in hypersensitivity pneumonitis: population attributable fraction. Issue 4 (5th October 2020) - Barnes, Hayley; Olin, Anna-Carin; Torén, Kjell; McSharry, Charles; Donnelly, Iona; Lärstad, Mona; Iribarren, Carlos; Quinlan, Patricia; Blanc, Paul D.
Background: Despite well-documented case series of hypersensitivity pneumonitis (HP), epidemiological data delineating relative contributions of risk factors are sparse. To address this, we estimated HP risk in a case-referent study of occupational and nonoccupational exposures. Methods: We recruited cases of HP by ICD-9 codes from an integrated healthcare delivery system (IHCDS) and a tertiary medical care centre. We drew referents, matched for age and sex, from the IHCDS. Participants underwent comprehensive, structured telephone interviews eliciting details of occupational and home environmental exposures. We employed a hierarchical analytic approach for data reduction based on the false discovery rate method within clusters of exposures. We measured lung function and selected biomarkers in a subset of participants. We used multivariate logistic regression to estimate exposure-associated odds ratios (ORs) and population attributable fractions (PAFs) for HP. Results: We analysed data for 192 HP cases (148 IHCDS; 44 tertiary care) and 229 referents. Occupational exposures combined more than doubled the odds of developing HP (OR 2.67; 95% CI 1.73–4.14) with a PAF of 34% (95% CI 21–46%); nonoccupational bird exposure also doubled the HP odds (OR 2.02; 95% CI 1.13–3.60), with a PAF of 12% (3–21%). Lung function and selected biomarkers did not substantively modify the risk estimates on the basis of questionnaire data alone. Discussion: In a case-referent approach evaluating HP risk, identifiable exposures accounted, on an epidemiological basis, for approximately two in three cases of disease; conversely, for one in three, the risk factors for disease remained elusive. Occupational and environmental factors account for two in three cases of HP. The contributions of risk factors vary markedly depending on case referral source. This could affect clinical ascertainment of cause and the implementation of preventative actions. https://bit.ly/3feAa6P